Firm-Level Evidenceon International Stock Market Comovement - Brooks, Robin (IMF Working Papers; Working Paper ;, 2003)
We explore the link between international stock market comovement and the degree to which firms operate globally. Using stock returns and balance sheet data for companies in 20 countries, we estimate a factor model that decomposes stock returns into global, country-specific and industry-specific shocks. We find a large and highly significant link: on average, a firm raising its international sales by 10 percent raises the exposure of its stock return to global shocks by 2 percent and reduces its exposure to country-specific shocks by 1.5 percent. This link has grown stronger since the mid-1980s.